(untitled) (Jurnal Sustainable, 2023)
The purpose of writing this journal is to examine models of change in organizations and find out whether incremental models can be used as solutions for change and development. This article selects literature study research methods and some previous research sources, and this study concludes that organizations must meet the basic principles in decision-making, namely ethics, orientation, scope, authority, credibility, and reference. In this case, organizational decisions are taken using several paradigms, namely the classical paradigm, administrative paradigm, incremental paradigm, administrative-incremental paradigm, and contingency paradigm. This article emphasizes that changing the organization is certainly not easy, especially for organizations with many times and a thick tradition. Most organizations make changes only to the vision and mission but not to the individuals and mindsets of their members. Any change can positively or negatively impact the organization’s internal and external environment. Of course, each organization member has a different mindset, and each individual must have different initial goals when first joining an organization. Therefore, a change must be flexible, effective, and accommodate all the wishes of organizational members, not just some groups.